2016
DOI: 10.5937/jrb1605005f
|View full text |Cite
|
Sign up to set email alerts
|

EURECA 2015: Serbia

Abstract: Sažetak Cilj:Analiza pojave, tretmana i ishoda srčanog zastoja kroz sprovedenu opservacionu studiju EuReCa 2015. u R.Srbiji. Metod: Podaci su prikupljeni u Službama i Zavodima za hitnu medicinsku pomoć tokom 2015. koji su se uključili u Prospektivni observacioni trijal Evropskog Resuscitacionog saveta, registrovan pod brojem NCT02236819 u bazi trijala i odobren od zdravstvenih autoriteta u SAD. U studiju su uključeni svi pacijenti -i odrasli i deca, koji su zatečeni mrtvi u vanbolničkim uslovima, a kod kojih j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
1
4
3
1
Order By: Relevance
“…4,8 This study reports the comparable annual incidence rate of 83.6/100,000, and previous reports of OHCA incidence in individual years imply that there is significant variability not only in time, but also in geographical distribution as well. [9][10][11] The results of this study are, however, lower than the incidence shown in the 2015 and 2016 reports from Serbia (160/100,000 and 122/100,000, respectively), 9,10 but are higher than the incidence reported from the first-half of 2017 (49.5/100,000). 11 All these reports analyzed data on all-aged patients, just like is the case in this report.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…4,8 This study reports the comparable annual incidence rate of 83.6/100,000, and previous reports of OHCA incidence in individual years imply that there is significant variability not only in time, but also in geographical distribution as well. [9][10][11] The results of this study are, however, lower than the incidence shown in the 2015 and 2016 reports from Serbia (160/100,000 and 122/100,000, respectively), 9,10 but are higher than the incidence reported from the first-half of 2017 (49.5/100,000). 11 All these reports analyzed data on all-aged patients, just like is the case in this report.…”
Section: Discussioncontrasting
confidence: 73%
“…11 It is also lower than the incidence in Serbia reported in the EuReCa One study (60/100,000) and previous European reports ranging from 3.26% to 6.85%. 7,8,24 The incidence of any ROSC achieved in the group of CPR attempted OHCA cases in 2015 and 2016 Serbian reports is higher compared to the result in this study of 7.01/100,000 (10.8/100,000 and 17.6/100,000, respectively), 9,10 but the present finding is comparable to the findings from the first-half of 2017 (7.0/100,000). Also, the percentage value of the same finding in this study (22.5%) is higher than the one from the 2014 Serbian database (16.1%), but is slightly lower to the result from the 2017 database (23.7%) 25 and the result of the Irish National Registry 2019…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Započete mere BLS-a (Basic Life Support) od strane očevica pokazuju veću šansu za preživljavanjem [3]. Postoji povezanost između zadesnih elemenata i ishoda VSZ, kao što su prisustvo svedoka, da li je svedok započeo mere reanimacije, kakav je bio inicijalni ritam, i drugi faktori [9]. Ciljevi rada su analiza učestalosti pojave VSZ i demografskih karakteristika reanimiranih pacijenata u Službi za hitnu medicinsku pomoć (SHMP) Pančevo u toku 2022. godine.…”
unclassified